2014
DOI: 10.1155/2014/185323
|View full text |Cite
|
Sign up to set email alerts
|

Angiosarcoma Arising in a Patient with a 10-Year-Old Hemangioma

Abstract: The transformation of a benign hemangioma into a malignant angiosarcoma has been rarely reported, with only 11 cases reported in the literature. There have been no reports of malignant transformation of hemangioma into angiosarcoma in association with epithelioid hemangioendothelioma, to our knowledge. The existence of precursor malignancies in the tumorigenesis of sarcomas is still not clearly defined. We describe the case of a 40-year-old woman with a preceding history of a suspected hemangioma for ten years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…An important indication is that most cancers develop later in life [ 130 ]. There are proliferative disorders such as benign hemangioma that, only on very rare occasions, transform into a malignant counterpart (i.e., angiosarcoma) [ 131 , 132 ], while other lesions, such as gastric mucosal intestinal metaplasia, have a higher risk of resulting in gastric cancer (i.e., 0.25% of the cases) [ 133 ]. For the latter, endoscopic surveillance every 1 to 2 years is needed as follow-up [ 134 ].…”
Section: Discussionmentioning
confidence: 99%
“…An important indication is that most cancers develop later in life [ 130 ]. There are proliferative disorders such as benign hemangioma that, only on very rare occasions, transform into a malignant counterpart (i.e., angiosarcoma) [ 131 , 132 ], while other lesions, such as gastric mucosal intestinal metaplasia, have a higher risk of resulting in gastric cancer (i.e., 0.25% of the cases) [ 133 ]. For the latter, endoscopic surveillance every 1 to 2 years is needed as follow-up [ 134 ].…”
Section: Discussionmentioning
confidence: 99%
“…2,8 Interestingly, several cases of composite hemangioendotheliomas have been reported which also include areas of low- to high-grade angiosarcomas. 8,9 Despite this, while local recurrence is common, typical composite hemangioendotheliomas are less aggressive than angiosarcomas with only 1 reported case of metastasis and death. 10 Given its nebulous definition and variety of presentations, there is question as to whether hemangioendotheliomas may represent a spectrum of disease from hemangioma to angiosarcoma, more benign or aggressive variants of angiosarcomas themselves, or entirely separate entities altogether.…”
Section: Discussionmentioning
confidence: 99%
“…However, the argument has been made that these lesions would likely be classified differently now as the cellular stage of capillary hemangiomas and not true angiosarcomas. 9 Nathenson et al 9 reported a more convincing case of soft tissue angiosarcoma arising from a hemangioma in the calf of a 40-year-old woman that had been present for 10 years. Pathology of this lesion demonstrated a cavernous hemangioma with multiple areas of high-grade angiosarcoma and an area of hemangioendothelioma.…”
Section: Discussionmentioning
confidence: 99%
“…They exhibit hematogenous spread with the lungs being the most common site for metastasis, followed by the liver, bones, soft tissues, and lymph nodes. The pathological diagnosis of angiosarcoma depends on the grading of tumorigenic cells either of high or low grade [ 10 ]. The overall survival rate ranges from 6 to 16 months [ 5 ].…”
Section: Discussionmentioning
confidence: 99%